Mapas mentais para o ensino de geografia: práticas e reflexões em uma escola de Campina Grande-PB - Almeida, David Luiz Rodrigues de (2015)
Currently in Brazil, the early years of primary education consists of five years (1st to 5th grade). This results, under the law, a longer period for literacy of subjects, from the age of six should enter school. Much has been invested in literacy Native language (Portuguese) and mathematics for basic training of students to the 3rd year. Moreover, little has been discussed about the progression of literacy in subsequent years. The presence of Geography in the school curriculum can aid the formation of the subjects, their world of reading, highlighting the cartographic literacy as methodology to thinking the geographical space from the place up other spatial scales. We emphasize that the School Cartography, which is dedicated to investigate the use of maps in geography teaching practices, attribute value in the production and reading of maps made by the students themselves. This potential is found in the use of mind maps, free representations, but guided by teachers aimed at inclusion, reflection and spatial readings treated at school. Based on these notes, this research aims to investigate the potential and limitations of the mental map resource for geography teaching and learning with students of 4th and 5th year of elementary school. For this we developed our research in the School Lucia of Fatima Gayoso Meira, in the city of Campina Grande - PB. Parallel to the use of mind maps developed theoretical and practical activities in order to motivate, present, build and reflect conceptual notions and skills with a group of 4 and another 5 years. For this research also rescued the considerations of school management, teachers and especially the students, using questionnaires and interviews. As a result we see the readings and understandings of the students regarding the organization of different scales of geographic space, now turned to their own daily life, sometimes the contents taught in the classroom. Also identified limits corresponding to the use of decontextualized contents, and that this knowledge is not related daily practices, there is no sense apprehends them which consequently may result in withholding or discouragement about learning geography in schools.